2019
DOI: 10.1002/aelm.201900393
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Devices and Circuits Based on Wafer‐Scale Polycrystalline Monolayer MoS2 by Chemical Vapor Deposition

Abstract: IntroductionRecently, 2D layered materials (2DLMs) have emerged as promising candidates for next generation nanoelectronic applications owing to their unique electronic properties and ultrathin 2D layered materials such as graphene and transition-metal dichalcogenides (TMDCs) have emerged as promising candidates for next-generation nanoelectronic applications due to their atomically thin thicknesses and unique electronic properties. Among TMDCs, molybdenum disulfide (MoS 2 ) has been extensively investigated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
47
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 56 publications
2
47
0
Order By: Relevance
“…The creation of those basic logic gates enables the organization of virtually any digital integrated circuits and opens up a scalable pathway to high‐performance logic applications using solution‐processable 2D semiconductor inks. Wang et al 182 demonstrated a practical approach to realizing fundamental building blocks for digital electronics based on large‐scale monolayer MoS 2 film synthesized via a CVD process. Ni foam was used as an acting barrier to limit the deposition rate of the precursor and improve the film uniformity.…”
Section: Synthesized Tmdcs For Electronicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The creation of those basic logic gates enables the organization of virtually any digital integrated circuits and opens up a scalable pathway to high‐performance logic applications using solution‐processable 2D semiconductor inks. Wang et al 182 demonstrated a practical approach to realizing fundamental building blocks for digital electronics based on large‐scale monolayer MoS 2 film synthesized via a CVD process. Ni foam was used as an acting barrier to limit the deposition rate of the precursor and improve the film uniformity.…”
Section: Synthesized Tmdcs For Electronicsmentioning
confidence: 99%
“…E, The detailed arrangement of substrate, precursor flow, and Ni foam. D,E, Reproduced with permission from Reference 182. F, Schematic of circuit fabrication on a MoTe 2 layer by conventional lithography and laser writing.…”
Section: Synthesized Tmdcs For Electronicsmentioning
confidence: 99%
“…Nickel oxide (NiO) foam was rst used as a barrier to control the deposition rate of Mo precursors on the substrate for the uniform growth of MoS 2 lms, but the evaporation rate was fast which led to uncontrollable reaction kinetics. 15,39 Moreover, the accelerated Mo release driven by the initial S evaporation, which prohibits the effective kinetics modulation, is yet to be addressed. To solve these problems, Shi et al 34 provided an oxide-inhibitor-assisted growth strategy to produce high-quality 2D Mo(S, Se, Te) 2 monolayer lms (Fig.…”
Section: Control Of Precursor Vapor Concentrationsmentioning
confidence: 99%
“…Besides, these solid transition metal salts can dissolve in water and then can be conveniently spin-coated on a substrate with uniform distribution. An annealing process at high temperature is needed to form the molten liquid precursor during the reaction, [38][39][40] which can be treated as a special liquid precursor. For example, Liu et al 41 introduced a molten-liquid intermediated CVD process for the growth of large-area TMDs with uniform thickness and a continuous monolayer (Fig.…”
Section: Control Of Precursor Vapor Concentrationsmentioning
confidence: 99%
“…Compared to silicon and other TMDs with a narrower bandgap, monolayer MoS 2 has a relatively wide bandgap (~1.8 eV) to enable a large current on/off ratio in its fieldeffect transistors (FETs) 32 . Now wafer-scale continuous MoS 2 films can already be synthesized by chemical vapor deposition (CVD) methods 33 and transferred to arbitrary substrates 34 . The device processing techniques have also been intensively investigated to address early criticism of 2D-FETs, such as the realization of Ohmic contact and integration of high-k dielectrics [35][36][37] .…”
mentioning
confidence: 99%